SGLT2 inhibitors improve plasma atherogenic biomarkers in patients with type 2 diabetes: a real world retrospective observational study - (:unkn) unknown (My University, 2021)
INTRODUCTION: There are cost-effective, non-invasive, and predictive tools used to predict the CVD risk in patients with diabetes such as the "atherogenic index of plasma (AIP)" which is defined as the logarithm to the base 10 of the ratio of fasting plasma TG (mg/dL) to HDL-C [log (TG/HDL-C)], triglyceride to high density lipoprotein (TG-to-HDL-C) ratio and the triglyceride glucose (TyG) index which is calculated as Ln (fasting TG (mg/dL) × fasting blood glucose (mg/dL)/2). These tools are indirect markers of atherosclerosis. Dapagliflozin and empagliflozin have exhibited cardiovascular beneficial effects and this study evaluated the effects of sodium glucose cotransporter 2 inhibitors (SGLT2i) on AIP, TyG index and TG-to-HDL-C ratio in patients with type 2 diabetes. METHODS: This single center, retrospective, observational study involved patients with type 2 diabetic patients who were prescribed SGLT2i in the endocrinology outpatient clinic between January 2017 and June 2019. Demographic and clinical data were collected from patient files. AIP, TyG index and TG-to-HDL-C ratio were calculated obtained at the first visit and the sixth month visit. RESULTS: Overall, 143 patients with T2DM (75 women, 68 men) were recruited in this study. Sixty six patients were prescribed dapagliflozin (46.2%), and 77 were prescribed empagliflozin (53.8%). SGLT2i treatment did not alter the lipid profile except the serum triglyceride (TG) levels. Serum TG levels were significantly reduced after 6 months of SGLT2i therapy (p = 0.045). All patients had significant reductions in AIP at 6-month follow-up (p < 0.001), accompanied by a significant reduction in TyG index (p < 0.001). Both empagliflozin and dapagliflozin caused significant decrease in AIP (p = 0.043 and p < 0.001, respectively) and TyG index (p = 0.010 and p < 0.001, respectively). CONCLUSIONS: Both dapagliflozin and empagliflozin were noted to significantly affect AIP and TyG indexes, which indicate atherosclerotic cardiovascular risk, with or without statin treatment regardless of lipid parameters.